Bacterias y hongos en el humo aspirado de cigarrillo - Olivo Lopez, José (2018)
Summary: Studies confirm the presence of potentially pathogenic microorganisms in leaf snuff. These could be reached by drag through the smoke to the airways and trigger a number of lung diseases. Therefore, the cigarettes could be considered a direct source of microorganisms that come to colonize the respiratory tract of active smokers, especially in immunosuppressed. The objective was to determine if bacteria and fungi in leaf snuff are drawn by aspirating smoke cigarettes. transversal and prospective study of non-experimental design. It was held in the Augustinian where 10 cigarette packets of two different brands (two groups of 5 packs) using a mechanical suction consisting of a flask Kitazato, graduated pipette, syringe 60ml, ducts and caps processed jebe. 10 packs analyzed brand A (5 packs), bacterial growth was obtained in 80% and the mark B (5 packs), 60% both corresponding to Bacillus sp. No molds and yeasts isolated. It is concluded that bacteria present in the leaf snuff are drawn through the cigarette smoke.